2018
DOI: 10.1001/jama.2018.0749
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia

Abstract: Hypothermia is a medical emergency; it occurs when a person is exposed to excessive cold temperatures.Hypothermia is defined by a core body temperature lower than 35°C (95°F). Below this temperature, the body loses more heat than it generates.Acute hypothermia occurs with immersion in cold water or exposure to cold weather. Chronic hypothermia occurs with certain diseases, aging, or prolonged exposure to cold temperatures. People with chronic illnesses, such as diabetes, arthritis, and preexisting heart condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Hypothermia is defined as a decrease in body temperature to less than 35 °C. Hypothermia is classified as mild (32–35 °C), moderate (28–32 °C), severe (25–28 °C), and profound (<24 °C) based on severity [ 64 ]. Given that MHT affects cell growth and survival, C2C12 cells were cooled to 32 °C for 3, 6, and 9 h. The results showed that MHT induced autophagy and mitophagy and upregulated O-GlcNAcylation in C2C12 cells, similar to the response to CS in vivo ( Supplementary Figure S1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothermia is defined as a decrease in body temperature to less than 35 °C. Hypothermia is classified as mild (32–35 °C), moderate (28–32 °C), severe (25–28 °C), and profound (<24 °C) based on severity [ 64 ]. Given that MHT affects cell growth and survival, C2C12 cells were cooled to 32 °C for 3, 6, and 9 h. The results showed that MHT induced autophagy and mitophagy and upregulated O-GlcNAcylation in C2C12 cells, similar to the response to CS in vivo ( Supplementary Figure S1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been well established that torpor bouts last longer at lower temperatures. For normal humans, a T b lower than 35°C leads to net loss of body heat and dysfunction in vital organs (Peiris, Jaroudi & Gavin, 2018). The brain can withstand temperatures lowered to 5–10°C, but can be damaged by temperatures below 5°C (Behringer et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for hypothermia (body temperature <95 °F) are exposure to cold temperatures, poor physical conditioning, exhaustion, lack of sufficient warm protective clothing, or predisposing health conditions (e.g., diabetes, hypothyroidism, hypertension, trauma, or consumption of drugs or illicit alcohol). [ 68,69 ] Hypothermia leads to symptoms such as shivering, slow pulse and breathing, slurred speech, exhaustion, and lack of coordination. [ 70–72 ] Prolonged exposure to cold stress can result in frost bite, trench foot, and chilblains.…”
Section: Wearables For Occupational Safety Monitoringmentioning
confidence: 99%